THE IMPORTANCE OF MOTHER CARE AND COLOSTRUM ON GROWTH RATES AND BODY MEASURMENTS IN AWASSI LAMBS - Al-Jalili, Zuhair F.; Hasoon, Tarik M. (The Iraqi Journal of Veterinary Medicine, 1999)
The growth and development in two groups of Aw-ssi lambs were followed from birth until weaning time. The first group did not received colostrum milk and divided in two equal sub group , the first was fed cow milk artificially, while the second sub group kept under mother care. Lambs in the control group (group 2) received colostrum and kept with their mother through - out the experimental period. Results indicated that lamb mortality was 20% in the first group while it was only 5 % in the control group. Average monthly body waight, body measurements and , weight at weaning time for lamb of the control group exceeded that of the first group and the differences were significant. Results also indicated that the second -sub-group showed better performance than the first sub-group although both of them received no colostrum , thus indicate the importance of mother care in the surviving of new born lambs